Impact of nurses’ health beliefs about caring for older adults on their own preparation for old age - Hwang, Se Jin; Gu, Minkyung; Shin, Saekyae; Sok, Sohyune (Frontiers in Public Health, 2025)
BackgroundThe older adults is increasing worldwide, and South Korea in particular is experiencing a rapid increase in the older adults. In this situation, related research targeting nurses who care for the older adult is necessary.ObjectiveThis study was to examine the relationships among preparation for old age and health beliefs, and the factors influencing preparation for old age of young nurses in their 20s and 30s who care for older adults in general hospitals.MethodsA cross-sectional descriptive design was employed. Participants were 110 nurses working in general hospitals, South Korea. Measures were the general characteristics list, the preparation scale for old age, and health belief scale.ResultsLevel of preparation for retirement (β = −0.53, p < 0.001), department (β = 0.34, p < 0.001), health beliefs (β = 0.32, p < 0.001), desired retirement age (β = 0.19, p = 0.022), annual salary (β = −0.18, p = 0.048), and chronic disease (β = 0.17, p = 0.028) were all statistically significant variables in the Step-2 regression model. Explanatory power was 69.2%.ConclusionImproving preparation for retirement and health beliefs could promote preparation for old age. Department, desired retirement age, annual salary, and chronic disease need to be considered when developing and implementing interventions for improving preparation for old age. Nursing managers or nurses need pay attention to factors influencing preparation for old age of young nurses caring for older adult patients in general hospitals.